Revolutionizing Blood Cancer Treatment: Emerging Therapies and Future Perspectives - Mritunjay Kumar Mahto; Zulphakar Ali; Kamalesh Mistry; Aftab Alam; Shesh Kumar; Komal Maliwal (International Journal of Biomedical Innovations and Engineering, 2025)
Blood cancer inclusive of leukemia, lymphoma and multiple myeloma poses a significant threat in the world today because of its multifactorial process and its non-amenable to standard therapies. Some of such approaches are immunotherapy, gene-editing technology and targeted small molecule inhibitors that have altered the nature of treatments. CAR T cell therapy is a molecular targeted therapy for cancers and several clinical studies have reported a huge success. Also, the immunotherapy has evolved with monoclonal antibodies and immune checkpoint inhibitors enhancing the rates of survival because of relapsed or refractory blood malignancies. Advanced technological tools like CRISPR-Cas9 offered a fresh way of eradicating gene disorders linked with hematologic malignancies. Of course, successes in hematopoietic stem cell transplantation associated with progress in regenerative medicine speak loudly and contributed to high improvement of treatment outcomes, especially among high risk patients. AI and machine learning have bypassed the drug development challenges in blood cancer treatment, strategized targeted therapies tailored for patients, and provide better diagnostic tests and biomarkers that will significantly enhance early diagnosis of the illnesses and there are issues that include therapy resistance, high costs of treatment, and issues of ethics of gene-editing technologies that still pose challenges. Forecast considering prospective future trends focuses on a versatile approach, introduction of combined therapy, and treatment methods that tailored to the patient’s condition. With the emergence of new generation therapies and utilizing artificial intelligence and precision medicine, the approaches to the treatment of blood cancer are on the verge of a revolutionary breakthrough true by plasma cell therapy, which gives hope for a long-term remission, and potentially cure.
Keywords: Blood cancer; Gene Editing; Leukemia; Lymphoma; Precision medicine; artificial intelligence; immunotherapy; multiple myeloma